Environmental Governance: Studying the Social Capital in Protected Areas - Cruz Coria, Erika; Zizumbo Villarreal, Lilia; Chaisatit, Nuchnudee Chaisatit (Universidad del Rosario, 2019)
In most Latin American countries, the decree of protected areas (pa) emerges as an instrument of nature conservation that is proposed by state policy. Therefore, the protected areas are under a management scheme carried out by the central government that limits the participation of other social actors and the sustainable use of resources in these territories. pa in Mexico are no exception, they are under a governance scheme in which the state stands as the central actor. Thus, this actor is responsible for regulating the access to and the use of these ecosystems that are of interest to multiple social actors. In this context, the objective is to propose some theoretical-methodological tools for understanding of the structure of social relations in the Mexican pa. This action is the basis for the design of planned interventions aimed at the development of environmental governance. For this paper, the theoretical perspective of social capital (sc) with emphasis on structural sc was used. This proposal has a broad capacity to explain the horizontal and vertical links in the whole structure of relationships. It allows the understanding of environmental governance as a multiactoral socio-organizational process.